Quality Standards for the Development, Application, and Evaluation of Measurement Instruments in Social Science Survey Research - Quality Standards Working Group (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2015)
[Introduction] Since its establishment in 2004, the German Data Forum (RatSWD), which is funded by the German Federal Ministry of Science and Research (BMBF), has been advising the federal government and the governments of the federal states (Länder) on issues relating to the expansion and improvement of the research infrastructure for the empirical social, behavioral, and economic sciences (SBE). In late 2010, the RatSWD addressed the question of how the quality of survey instruments in the social and economic sciences, and especially in social and economic survey research, could be controlled and assured. At a meeting on November 9, 2012, the RatSWD therefore decided to set up a 'Quality Assurance of Survey Instruments Working Group' under the leadership of Professor Beatrice Rammstedt. The establishment of the working group was prompted in particular by the desire to define quality standards in order to assure and optimize the quality of survey instruments. Hence, the working group made the formulation of these standards its primary objective. They are presented in this paper.
Keywords: 330